Modernity and parrhesia. Michel Foucault and the question of resistance as ethos - Giraldo Díaz, Reinaldo (Estudios de Filosofía, 2011)
In this research article the elaborations on truth-telling from Michel Foucault are hold, which are inscribed in the context of concerns about the present. The analysis of the French philosopher of antiquity did not seek to formulate the theory of power or of an universal and abstract subject, but to show the historical constitution of the different forms of subject in relation to the games of truth, reveal the contingent nature of our goals and of our history and to show a power to resist to the subjection mechanism from West.